QUALITY IMPROVEMENT AND TESTING OF PROCESSED FOOD PRODUCTS OF SMALL AND MEDIUM ENTERPRISES (SME) IN SIDAMULIH VILLAGE, PANGANDARAN DISTRICT, WEST JAVA - Suliasih, Neneng; Sumartini, Sumartini; Widjaya, Willy Pranata; Tristantio, Sidik; Ramadhan, Roiyhan Shyma; Ghaffar, Rizal Maulana (LPPM Univ. Ibn Khaldun Bogor, 2024)
The people of Sidamulih village have sufficient interest, expertise and appropriate and renewable technology, but there is no special guidance for small community business groups. Several groups of Micro, Small and Medium Enterprises of processed food products are constrained in marketing to a wider scope such as to super markets, due to suboptimal product quality and the absence of product information such as nutritional content and product expiration date. This is due to constraints on testing costs and MSMEs' ignorance of the importance of food product quality. The existence of tourism group coaching activities and community institution coaching activities that are still active in improving and testing the quality of processed food products of MSMEs are expected to bridge the interests of the community, especially MSMEs of processed food products to expand their marketing due to increased consumer confidence in product safety. The test results show that the nutritional content of processed MSME products varies, some products have good quality, some are not good. A similar thing happens with product expiry, where some have expiry periods that are too short, making them less suitable for long-term marketing. This problem needs to be followed up with briefings to related MSMEs on good food processing methods, so that processed MSME products will be of better quality and marketable. The next plan is to conduct training on Good Processed Food Processing Methods for MSMEs so that processed products will have better quality so that their marketing is wider.